Neurocognitive effects of binge drinking on verbal episodic memory. An ERP study in university students - Rodríguez Holguín, Socorro; Folgueira-Ares, Rocío; Crego, Alberto; López-Caneda, Eduardo; Corral, Montserrat; Cadaveira, Fernando; Doallo, Sonia (Frontiers in Pharmacology, 2023)
Background: Verbal memory may be affected by engagement in alcohol binge drinking during youth, according to the findings of neuropsychological studies. However, little is known about the dynamics of the neural activity underlying this cognitive process in young, heavy drinkers. Aims: To investigate brain event-related potentials (ERPs) associated with cued recall from episodic memory in binge drinkers and controls. Methods: Seventy first-year university students were classified as binge drinkers (32: 17 female) or controls (38: 18 female). The participants completed a verbal paired associates learning task during electroencephalogram (EEG) recording. ERPs elicited by old and new word pairs were extracted from the cued-recall phase of the task by using Principal Component Analysis. Subjects also performed a standardized neuropsychological verbal learning test. Results: Two of the three ERP components indicating old/new memory effects provided evidence for anomalies associated with binge drinking. The old/new effects were absent in the binge drinkers in the two subsequent posterior components, identified with the late parietal component (LPC) and the late posterior negativity (LPN). The late frontal component revealed similar old/new effects in both groups. Binge drinkers showed similar behavioural performance to controls in the verbal paired associates task, but performed poorly in the more demanding short-term cued-recall trial of a neuropsychological standardized test. Conclusions: Event-related potentials elicited during a verbal cued-recall task revealed differences in brain functioning between young binge drinkers and controls that may underlie emergent deficits in episodic memory linked to alcohol abuse. The brain activity of binge drinkers suggests alterations in the hippocampal - posterior parietal cortex circuitry subserving recognition and recollection of the cue context and generation of the solution, in relation to verbal information shallowly memorised.